Islamic Boarding School-Based Economic Empowerment in Jember District The One Islamic Boarding School One Product (OPOP) Program - Miftahul Ulum; Nurul Widyawati IR; Abdul Wadud (Jurnal Syntax Admiration, 2023)
As a subcultural institution that is deeply rooted and embedded, the existence of Islamic boarding schools cannot be separated from the discourse on education in Indonesia. Islamic boarding school institutions have a strategic position because they deal directly with the community and not only educate, but also empower the community. As mandated in the Presidential Law of the Republic of Indonesia No. 18 of 2019 concerning Islamic Boarding Schools in article 4, it is stated that Islamic boarding schools function as educational institutions, missionary institutions and community empowerment . The One Pesantren One Product (OPOP) program which started in 2019 is part of the East Java Provincial government program which also carries out the mandate of the law related to community empowerment. This research uses a qualitative approach with descriptive research type. This research was located in two OPOP member Islamic boarding schools. There are three basic questions in this research. First, how to implement Islamic boarding school-based economic empowerment in Jember Regency through the One Pesantren One Product program (OPOP)? Second, what is the impact of Islamic boarding school-based economic empowerment in Jember Regency through the One Pesantren One Product program (OPOP)? And third, what are the supporting and inhibiting factors for Islamic boarding school -based economic empowerment in Jember Regency through the One Pesantren One Product program ? (OPOP)? . This research aims to find out how it is implemented, its impact, as well as supporting and inhibiting factors. The results of this research show that the benefits of this program can be felt significantly by OPOP member Islamic boarding schools.